Study of Chronic Diseases (Edoc): methodological aspects - Thatiana Lameira Maciel Amaral; Cledir de Araújo Amaral; Margareth Crisóstomo Portela; Gina Torres Rego Monteiro; Maurício Teixeira Leite de Vasconcellos (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: Describe the sampling design and other methodological aspects of the Study of Chronic Diseases (Edoc). METHODS: Edoc comprises two household surveys with distinct populations, one with adults aged 18 to 59 years (Edoc-A) and another with older adults aged 60 years or more (Edoc-I), living in Rio Branco, Acre. The selection of the participants used complex samples by clusters in two stages of selection, census enumeration areas (CEA) and household. In the first stage, common to both surveys, 40 CEAs were selected with probability proportional to size, and in the second stage, independent for each survey, households were selected with equal probability, and all the residents eligible for each survey were selected. Sampling weights were estimated by the inverse of the product of inclusion probabilities at each stage and then calibrated to produce unbiased population estimates. Interviews were held with questionnaires about socioeconomic and demographic conditions, life habits and health conditions. Anthropometric measures focused on measures of body height, girths and mass, while the vital signs analyzed were blood pressure, heart rate and respiratory rate. Blood and urine samples were collected for analysis. RESULTS: The Edoc comprised 1,701 participants, 685 of Edoc-A and 1,016 of Edoc-I. Considering the loss of information of some participants and the need of studying specific themes with production of population inferences, 16 subsamples of complete information by theme were generated and two subsamples were exclusive of Edoc-I. CONCLUSIONS: The Edoc has as important developments the analyses of epidemiological profile of the population from the capital of the state of Acre, contributing to the production of knowledge in public health with useful information for decisions in public health policies.